In vitro cytotoxicity and in vivo-biocompatibility of contemporary resin-modified glass-ionomer cements - Souza, Pedro P. C.; Aranha, Andreza M. F.; Hebling, Josimeri; Giro, Elisa M. A.; de Souza Costa, Carlos A. (Elsevier B.V., 2006)
Objectives. To evaluate the effects of current resin-modified glass-ionomer cements (RMGICs) applied on culture of cells or implanted into subcutaneous tissue of rats.Methods. Experiment 1 - Thirty round-shaped samples of every RMGICs: Rely X Luting Cement (RL), Vitremer (VM), and Vitrebond (VB) were placed into wells with 1.1 mL of culture medium (DMEM), and incubated for 24,48 or 72 h. The extracts from every sample were applied on the MDPC-23 cells. Fresh DMEM was used as control group. The MTT assay was carried out for mitochondrial respiration. Experiment 2 - Fifty-four polyethylene tubes filled with the experimental materials were implanted into the dorsal subcutaneous tissue of rats. At 7, 30, and 90 days the animals were killed and the biopsies were processed for histological evaluation.Results. Experiment 1 - Both time of elution and material significantly influenced cell respiratory activity. in general, the extracts obtained at 24 h were less cytotoxic than 48 and 72 h incubation. The cytotoxic effect of VM and RL were not statistically different (P < 0.05) for the 24-hour period. VB showed the highest cytotoxic effect. Experiment 2 - All RMGICs elicited at 7 days a moderate to intense inflammatory reaction which decreased over time. However, connective healing occurred for most of samples at 90-day evaluation.Significance. Glass-ionomer cements may cause noticeable inflammatory response when in direct contact to connective tissue. The toxic effects of this kind of soluble material depend on the amount of components released in the aqueous environment. (C) 2005 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
Keywords: biocompatibility; glass-ionomer cement; cytotoxicity; cell culture